2006
DOI: 10.1542/peds.2004-2702
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Pediatric Trauma Stabilization in 35 North Carolina Emergency Departments: Identification of Targets for Performance Improvement

Abstract: This study used simulation to identify deficiencies in stabilization of children presenting to EDs, revealing that mistakes are ubiquitous. ED personnel were universally receptive to feedback. Future research should investigate whether interventions aimed at improving identified deficiencies can improve trauma stabilization performance and, ultimately, the outcomes of children who present to EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…While our results represent an improvement from previously reported exposure compliance rates in pediatric trauma simulation (3Y16.7%), they fail to reach universal compliance as recommended in the ATLS protocol. 15,16 To be considered compliant with the exposure task in this study, we required the removal of all clothing before blanket placement. We chose this definition based on our observation that once a blanket is placed, full visualization of the patient rarely occurs during the resuscitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our results represent an improvement from previously reported exposure compliance rates in pediatric trauma simulation (3Y16.7%), they fail to reach universal compliance as recommended in the ATLS protocol. 15,16 To be considered compliant with the exposure task in this study, we required the removal of all clothing before blanket placement. We chose this definition based on our observation that once a blanket is placed, full visualization of the patient rarely occurs during the resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…14Y16 During simulated pediatric trauma resuscitations, 97% of trauma teams failed to fully expose the mannequin or attempt warming methods such as placement of warm blankets or external warming devices. 15 Video review of low-acuity adult trauma resuscitations found that one third of teams failed to expose the patient or make use of warm blankets to prevent hypothermia. 17 Only 3% of these teams measured the patient's temperature, suggesting a lack of focus on this aspect of the resuscitation.…”
mentioning
confidence: 99%
“…However, observational studies have demonstrated that health care professionals do not always adhere to ATLS guidelines. 32 A recent study described marked variation in the clinical performance of ED professionals in a simulated pediatric trauma event. 32 Resuscitation tasks associated with both the primary survey (a quick examination to identify life-or limb-threatening injuries) and the secondary survey (a complete head-to-toe examination to identify all signs of injury) were often skipped or performed incompletely by the ED team.…”
Section: Best Practice In Emergency Stabilization and Resuscitationmentioning
confidence: 99%
“…Medical simulation was used also to identify deficiencies in the stabilization of children presenting to emergency departments, revealing that mistakes, including estimating a child's weight, preparing for intraosseous needle placement, ordering intravenous fluid boluses, and applying warming measures, are ubiquitous [43]. In another study, the findings of major deviations in airway management, and in the evaluation of secondary respiratory and hemodynamic deterioration in the intubated trauma patient, were followed by changes in the training curriculum and, as a consequence, improvement in performance [44].…”
Section: Computerized Patient Simulatorsmentioning
confidence: 99%